Lifespan in the progeny of Drosophila melanogaster after acute γ-irradiation - СкоробагатькоД. O.; Страшнюк, В. Ю.; МазіловO. O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
Lifespan (LS) of adults of Drosophila melanogaster in the F1 generation after a single acute exposure of parents to bremsstrahlung γ-rays was studied. Wild-type stock Oregon-R was used as the material. 3-day-old adults were irradiated with bremsstrahlung gamma-rays at doses of 8 Gr, 16 Gr and 25 Gr using the electron linear accelerator LUE-10. Irradiated (I) and non-irradiated (C) flies were crossed in four different combinations: C×C (control), I×C, C×I, and I×I. The effects depended on the dose of radiation, sex of irradiated flies and F1 offspring sex. The most effective dose was 25 Gr, the effect occurred in all exposure variants (I×C, C×I, and I×I). The LS usually increased, except for females I×I, who lived less then control flies. The statistical power of the influence of the radiation dose on the LS of adults in different variants of the experiment was 2,7–10,0 % except females F1 I×I, in which no significant influence of the radiation doses on the investigated trait was revealed.